Note on a Possible OB Association in Scorpius - Pik Sin The (Journal of Mathematical and Fundamental Sciences, 1961)
During a survey of HÎ±-emission stars, a clustering of OB  and A-type stars was noticed in the constellation Scorpius.  It is believed that these stars form a new association extending in R.A. from 17h00m to 17h16m (1900) and in Dec. from -31°30' to -34°30' (1900). The distance to this association is probably 1400 psc.In the course of recent survey of HÎ±-emission stars (1) in the vicinity of the emission nebulosities NGC 6334 and NGC 6357, the author noticed a clustering of HÎ±-emission stars to the north of dark nebula.  This nebula is believed to form a connection between the two emission nebulae. The group of HÎ±-emission stars is centered about the HÎ±-emission stars HD 155806 (R.A.= 17h08.m7, Dec.=-33Ëš26';1900), which is classified as Oe5p in the Henry Draper extension, while in the Henry Draper Catalog it is classified as B3p.A total of 13 HÎ±-emission stars were found in circular area of 1,5 degree radius, centered on the star HD 155806. Two of these stars are of late spectral type, six are early spectral type, and the remaining five are too faint to classify on both red and blue plates. They might possibly be T-Tauri type star, as may also be the case for the faint HÎ±-emission stars which are seen projected on the dark nebulosity mentioned above.It is well known that T associations are sometimes found together with OB associations. In order to determine whether or not an OB associations exists together with the above mentioned possible T association, the author made a preliminary search for such an association in circular area of one degree radius centered on the star HD 155806. Chart No. 180 in the Henry Draper Extension was used for this survey. Within the prescribed area,  49 OB-Type and 85 A-type stars were found.The corresponding surface densities are thus 15.6 and 27.0 stars per square degree